2015
DOI: 10.1534/genetics.115.176438
|View full text |Cite
|
Sign up to set email alerts
|

An Rtf2 Domain-Containing Protein Influences Pre-mRNA Splicing and Is Essential for Embryonic Development in Arabidopsis thaliana

Abstract: Alternative splicing is prevalent in plants, but little is known about its regulation in the context of developmental and signaling pathways. We describe here a new factor that influences pre-messengerRNA (mRNA) splicing and is essential for embryonic development in Arabidopsis thaliana. This factor was retrieved in a genetic screen that identified mutants impaired in expression of an alternatively spliced GFP reporter gene. In addition to the known spliceosomal component PRP8, the screen recovered Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 48 publications
(82 reference statements)
5
75
0
Order By: Relevance
“…In contrast to smu1-4 and cwc16a-1, the two GFP-weak mutants reported here, prp8-10 and rtf2-4 showed generally reduced splicing efficiency of GFP premRNA, leading to increased accumulation of the unspliced primary transcript. The overall reduced splicing efficiency in these mutants is consistent with core spliceosomal roles of PRP8 (Pleiss et al 2007) and possibly RTF2 (Larson et al 2016), although a regulatory role through ubiquitination has also been suggested for RTF2 (Sasaki et al 2015).…”
Section: Mechanistic Aspects Of Smu1 and Cwc16a Activity In Splicingsupporting
confidence: 69%
See 3 more Smart Citations
“…In contrast to smu1-4 and cwc16a-1, the two GFP-weak mutants reported here, prp8-10 and rtf2-4 showed generally reduced splicing efficiency of GFP premRNA, leading to increased accumulation of the unspliced primary transcript. The overall reduced splicing efficiency in these mutants is consistent with core spliceosomal roles of PRP8 (Pleiss et al 2007) and possibly RTF2 (Larson et al 2016), although a regulatory role through ubiquitination has also been suggested for RTF2 (Sasaki et al 2015).…”
Section: Mechanistic Aspects Of Smu1 and Cwc16a Activity In Splicingsupporting
confidence: 69%
“…Whether SMU1 has this activity in Arabidopsis remains to be investigated. Several Arabidopsis splicing factors acquire ubiquitination, including the catalytic site core protein PRP8, which was identified among the GFPweak mutants in our screens (Sasaki et al 2015; this study). Homozygous smu1-1 and smu1-2 T-DNA insertion mutants of Arabidopsis were reported to be nonviable or show multiple, nonlethal developmental defects, respectively (Chung et al 2009).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…S2B). A recent study showed that Arabidopsis Prp8 is involved in modulating the splicing of the GFP reporter gene in a genetic screen (28) and long noncoding transcript COOLAIR to regulate FLC transcription (25). Protein sequence alignment of Prp8 homologs showed that P1141 of Prp8 is in the linker region between the RNA recognition motif (RRM) and the U5-snRNA binding domain and is highly conserved from yeast to humans, and P347 is in the linker region between the N-terminal domain and the PROCN domain and is moderately conserved (Fig.…”
Section: Point Mutations In Prp8 Are Responsible For Suppressors Of Amentioning
confidence: 99%